Theoretical model for calculating and adjusting radon activity concentration in ventilation networks of uranium mines considering pressure drop effect - Ye, Yongjun; Shang, Shanwei; Zhang, Yingpeng (Journal of environmental radioactivity, 2024)
The radiation dose of workers in underground uranium mines mainly comes from radon and radon progeny. To ensure a healthy and safe work environment, it is necessary and urgent to optimize the design of ventilation systems. As such, based on the simplified radon diffusion-advection migration model of the rocks, this paper proposes 1) two methods for determining the radon exhalation rate modified by pressure drop, 2) three methods for calculating radon activity concentration of single-branch, and 3) the novel adjustment algorithm and solving procedures for calculating and adjusting the radon activity concentration in ventilation networks by modifying the radon exhalation rate, demonstrated on a specific ventilation network in a simulated underground uranium mine with calculation and analysis via MATLAB. The results show that 1) the radon exhalation rate of different branches can be modified by their pressure drop, and 2) the proposed method can be used to reveal the influences of different ventilation methods and fan pressures on the radon activity concentration in the ventilation network and the radon release rate to the atmosphere. •Two methods to modify the radon exhalation rate of roadway-surrounding rocks by pressure drop were developed.•Three methods were proposed for reasonably calculating the radon activity concentration in single branch.•The novel adjustment algorithm and solving procedures for analyzing radon-containing ventilation networks were established.•The ventilation methods and its operating parameters of radon reduction were evaluated and optimized.